2020
DOI: 10.4317/medoral.23350
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular incisive canal-related prevalence, morphometric parameters, and implant placement implications: a multicenter study of 847 CBCT scans

Abstract: Background: This study evaluated the epidemiological and morphological features of the mandibular incisive canal (MIC) using cone beam computed tomography (CBCT) in a significant sample of subjects in Brazil. Material and Methods: This retrospective, multicenter study assessed 847 CBCT scans performed at four oral imaging centers. The sample comprised CBCT images acquired from dentate individuals who presented at least from tooth 35 to tooth 45 in the anterior mandible region. Data regarding patient sex and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
5
14
0
1
Order By: Relevance
“…Detailed preoperative study of anatomical structures with cone-beam computed tomography is crucial for the success of the procedure and to reduce the number of postoperative complications after procedures in the area of the synphysis. Several studies have shown that, due to its excellent anatomical resolution, this test is the best method for obtaining incisor canal and for preoperative measurements, due to its reproducibility and high degree of reliability, results similar to anatomical studies in dry skull have been obtained [16], [17].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Detailed preoperative study of anatomical structures with cone-beam computed tomography is crucial for the success of the procedure and to reduce the number of postoperative complications after procedures in the area of the synphysis. Several studies have shown that, due to its excellent anatomical resolution, this test is the best method for obtaining incisor canal and for preoperative measurements, due to its reproducibility and high degree of reliability, results similar to anatomical studies in dry skull have been obtained [16], [17].…”
Section: Introductionmentioning
confidence: 80%
“…All images were processed and worked on on Demand3d® (Cybermed, Seoul, Republic of Korea). These procedures were performed according to the protocol described above by Barbosa et al 2020 [17] as shown in Fig. 1.…”
Section: Mic Extension Analysismentioning
confidence: 99%
“…In clinical practice, the most commonly used radiological technique for morphological assessment of the MIC is cone-beam computed tomography (CBCT) [ 3 , 4 , 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the presence, size, and position of the MIC on CBCT images [ 1 , 2 , 3 , 4 , 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, to our knowledge, no CBCT study has evaluated the presence, size, and distance of the MIC from adjacent anatomical landmarks, and the observer variability of MIC measurements, in the dentate mandibles of Caucasian (Italian) patients.…”
Section: Introductionmentioning
confidence: 99%
“…It enters the mandible through the mandibular foramen and travels to the mental foramen and may make a loop by running upward and backward before creating the mental foramen [ 5 ]. With regard to the mandibular canal, several investigations have noted that an extension of the mandibular canal called the mandibular incisive canal may locate mesial to the mental foramen, which can be in danger during implant insertion as well [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%